Effect of Copper, Zinc and Lead and Their Combinations on the Germination Capacity of Two Cereals - Tomulescu, Ioana Mihaela; Radoviciu, Edith Mihaela; Merca, Vasilica Viorica; Tuduce, Adela Dana (Acta Agraria Debreceniensis, 2004)
The majority of researchers have studied the following group of microelements: B, Zn, Mn, Cu, Na, Co, Mo, I, Sn, Cl, Al, V, F, Cr, Hg, Cs, Li, Cd, As, Th, Rb, Cr, W, Ti, Sn, Se, Ba, Br. Sporadically, the following elements have been mentioned too: Au, Ra, Hg and Pb. In this study, the effects of copper treatments and their combination with zinc and lead microelements on the germination of maize and barley were investigated using different concentrations of these microelements. Six treatments were used: 1. Copper-sulphate (CuSO4) applied alone, 2. Zinc-sulphate (ZnSO4) applied alone, 3. Copper applied with zinc, 4. Lead-nitrate (Pb(NO3)2) applied alone, 5. Copper applied with lead and 6. Untreated control. Maize (Kiskun SC 297) and barley caryopsis were treated with copper and zinc solutions in the following concentrations: 0.03%, 0.003% and 0.0003%. Maize and barley caryopsis were treated with these solutions for 12 and 24 hours. Maize and barley caryopsis were also treated with lead solutions Pb(NO3)2 with different concentrations: 0.0005%, 0.005% and 0.05%. Maize and barley were treated with these solutions for 12 and 24 hours. In the combined treatments (3 and 5), the same concentration was used for each microelement as in treatments 1, 2 and 4. Control treatments were treated with water for both plant species. Our results showed that copper microelements significantly inhibit germination compared to the untreated control. The toxicity of copper is higher if concentration increases. Zinc microelements also inhibit germination, however its effect highly depends on the microelement concentration. Treatments of copper + zinc also inhibit germination. The two microelements applied together cause more phytotoxicity than they do alone. Lead is highly toxic to plants even in low concentrations. The toxic effect on germination dramatically increased when lead was applied with copper.